PENDEKATAN PRAGMATIS DALAM PENDIDIKAN ISLAM: (KAJIAN TERHADAP TEORI AL-DZARA’I’ DALAM FILSAFAT PENDIDIKAN ISLAM) - Mundzar Fahman; M. Amruddin Latif; suudin aziz (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
The idea of ​​renewal in Islam, Islamic philosophy, philosophy of Islamic education, and contemporary Islamic thought lies in the extent to which these sciences can interact and dialogue with new developments in Islamic discourse. Educational reform has pragmatically placed education as an inseparable part of changing the mindset and life of mankind. In the repertoire of Islamic education, the pragmatic theory of education is known as al-Dzara'i theory. Education and science must create a skill. Skills develop following the development of progress and prosperity according to the context of the times and regions, as the main capital for community development, when the profession in society has developed in a complex manner, a science teaching is needed that aims to acquire and develop the skills required by a required profession. Pragmatism in education is the result of human existence in absorbing the outside world into oneself (internalization), then interpreted (subjectification) using reason and mind with the help of science, and then re-expressed to the outside world (objectification) through the process of externalizing and legitimizing it. Education is the conception of individual and group interpretation activities in forming a particular skill.